Gertrude Stein, Modernism, and the problem of "genius" - Will, Barbara (Edinburgh University Press, 2000)
"This book examines the centrality and the specificity of the idea of "genius" to Stein's work in particular and to the aesthetic ideals and contradictory intellectual affiliations of high modernism in general. Through a chronological reading, it maps Stein's move from an early investment in an essential and essentializing notion of "genius" to her later use of the term to describe an anti-essentialist, democratic textual process. It considers how this revisionary idea of "genius" evolved out of Stein's complex identification of herself as Jewish, queer and American. And it ends with Stein's seemingly paradoxical decision to call a text about being a genius in America, Everybody's Autobiography."--Jacket